Health and medical device development for fundamental care: Scoping review. Issue 11 (1st October 2019) - Matinolli, Hanna‐Maria; Mieronkoski, Riitta; Salanterä, Sanna
Abstract: Background: The use of technology and health and medical devices as a part of fundamental nursing care is increasing. Although involving users in the device development process is essential, the role of nurses in the process has not yet been discussed. Objectives: To examine and map what kind of health and medical devices have been developed specifically for fundamental nursing care and to examine the design and development of the devices, particularly focusing on the role of nurses in the process. Design: Scoping review. Data sources: The Medline, Cinahl, Web of Science, IEEE Explore and ACM DL databases Review methods: The databases were searched to identify studies describing health and medical devices developed for fundamental nursing care published between the years 2008–2018 in English language. References of included articles were reviewed for additional eligible studies. Two research team members screened the abstracts and full articles against the predefined inclusion and exclusion criteria. The PRISMA‐ScR checklist was used. Results: Of the 7223 reports identified, a total of 19 were chosen for the scoping review. Of these, five were further analysed regarding the development process. Main focus areas of the included reports were patient monitoring, pressure ulcer prevention and patient transfer and mobility. Device development process, divided into three phases, was mainly driven by technological expertise and healthcare personnel were mainly involved in the evaluation phases. Conclusions: Health and medical devices are a crucial part of the healthcare today and nurses are increasingly involved with their use. Most of the devices have been developed mainly by using technological expertise although they are directly aimed at fundamental aspects of nursing care. The results of our review suggest that the expertise of the nurses as the end‐users of the devices could be much more exploited. Relevance to clinical practice: A combination of expertise of device development from both nursing professionals and technical experts is necessary to disentangle the requirements of increased quality in nursing care combined with the ever‐growing technological requirements.